Towards Information Transparency in the Context of Service Management - Belter, Roman; Spies, Thorsten; Ludwig, Andre; Franczyk, Bogdan; Eicker, Stefan (Proceedings of the IEEE International Conference on Service-Oriented Computing and Applications (SOCA), 2010, 2010)
With an increasing demand for higher value services, comprehensive support for service customization, provisioning and management is needed. This paper details ongoing research work regarding a service management approach, which supports the handling of service artifacts during the service lifecycle. The approach introduces an information model for e-Service Management, as well as a tailored view concept to provide individual views to participating stakeholders. The outlined approach tackles nonfunctional management issues which lead to better maintainable, adaptable and extendable service systems.
Keywords: service management; generic views; service system; artifacts; service stakeholder